The Psychometric Proprieties of the Jordanian Version of the Childhood Autism Rating Scale – Second Edition (CARS2-HF) - Hemedan, Nabil; Maharmeh, Lina (Dirasat: Human and Social Sciences, 2022)
The purpose of this study was to verify the psychometric proprieties of the Jordanian version of the Childhood Autism Rating Scale - HF (second edition) to diagnose the individuals with high functional autism spectrum disorder, on a sample of (20) students distributed in three districts areas in Jordan ranging from (6-18) years, including (10) high functional autistic students, (5) students with ADHD, and (5) ordinary. The scale was applied to the previous sample after being presented to a group of arbitrators and practitioners in the field. The results showed that the measure have an excepted level of contend validity, where the correlation of paragraphs with the instrument as a whole ranged from (0 – 0.92), and the discriminatory honesty through the existence of statistically significant differences (∞ = 0.05) between the ordinary students on the one hand and other students; On the other hand the differences came in favor of both students with ASD-HF, ADHD, as shown by statistically significant differences between students with ASD-HF, ADHD and there were also statistically significant differences between students with ASD-HF, ADHD, and the differences were in favors of students with ASD-HF, while persistence in internal consistency was calculated by calculating the alpha-Cronbach equation (0.96). Also the results showed the existence of another characteristic of scale such as objectivity, ease of application, correction and interpretation of results